2017
DOI: 10.1530/joe-16-0104
|View full text |Cite
|
Sign up to set email alerts
|

Expression of wnt4/5 during reproductive cycle of catfish and wnt5 promoter analysis

Abstract: Signaling molecules, Wnt4 and Wnt5, are essential for ovarian growth during developmental stages in mammals. Although these molecules were identified in several teleosts, their precise expression and role in reproductive processes have not yet been explored in any lower vertebrates. In view of this, using catfish, Clarias batrachus as an animal model, cloning and expression analysis of wnt4 and wnt5 were analyzed in different tissues, at various developmental stages, during ovarian reproductive cycle and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The wnt signaling pathway is a conservative signaling network, which takes part in embryonic development, cell differentiation and proliferation, and the process of growth regulation [63]. As a signaling factor, Wnt5 plays various roles in vertebrate development [6467]. Importantly, Wnt5 could coordinate with Wnt4 to initiate the meiosis for ovarian follicular growth in mammals [68].…”
Section: Discussionmentioning
confidence: 99%
“…The wnt signaling pathway is a conservative signaling network, which takes part in embryonic development, cell differentiation and proliferation, and the process of growth regulation [63]. As a signaling factor, Wnt5 plays various roles in vertebrate development [6467]. Importantly, Wnt5 could coordinate with Wnt4 to initiate the meiosis for ovarian follicular growth in mammals [68].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, differences in the expression of various ROR1 and TLR4 ligands are related hormonally during reproductive activity in different species, suggesting that ROR1 and TLR4 expression may be regulated by multiple ligands during the cycle. For example, Wnt5, a ligand of ROR1, changed during the ovarian reproductive cycle in the catfish ovary, with a peak during the spawning phase (Prathibha & Senthilkumaran 2017), while heat-shock protein (HSP60), a ligand of TLR4, changed its own expression during rat ovarian follicle growth (Paranko et al 1996). Furthermore, we observed cytoplasmic immunolocalisation of resistin, ROR1, and TLR4 in luteal cells.…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies have suggested that Wnt5 plays various roles in vertebrate development and participates in initiating meiosis for ovarian follicular growth in mammals [ 49 , 50 , 51 , 52 ]. However, in invertebrates, Wnt5 shows a completely different function.…”
Section: Discussionmentioning
confidence: 99%